A circular inclusion with inhomogeneous sliding imperfect interface in harmonic materials (Archives of Mechanics - Test, 2018)
In the following study we rigorously analyze the problem of a circular inclusion with inhomogeneous imperfect sliding interface in finite deformation of harmonic materials. The work begins by defining the inhomogeneous sliding boundary conditions characterized by two interface parameters corresponding to the normal and tangential coordinate directions (with respect to the interface boundary curve), respectively. Then, through the process of analytic continuation the problem is eventually reduced to the determination of a single analytic function given by an ordinary differential equation with variable coefficients. A specific example is selected to illustrate the method. The effects of the circumferential variation of the interface parameter on the mean stress at the interface and the average mean stress in the inclusion are discussed.